2017
DOI: 10.1016/j.actbio.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

ECM turnover-stimulated gene delivery through collagen-mimetic peptide-plasmid integration in collagen

Abstract: Gene therapies have great potential in regenerative medicine; however, clinical translation has been inhibited by low stability and limited transfection efficiencies. Herein, we incorporate collagen-mimetic peptide (CMP)-linked polyplexes in collagen scaffolds to increase DNA stability by up to 400% and enable tailorable in vivo transgene expression at 100-fold higher levels and 10-fold longer time periods. These improvements were directly linked to a sustained interaction between collagen and polyplexes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 78 publications
1
36
0
Order By: Relevance
“…In particular, we demonstrated previously that GPP‐modification of PEI polyplexes greatly enhanced control over both the extent and duration of transgene expression through utilization of the reversible, serum‐stable affinity between CMPs and natural collagen. Enhanced control and activity were demonstrated both in vitro and in vivo, using a murine subdermal repair model . Additional studies concluded that these improvements were the result of superior serum‐stability and endocytic trafficking driven by increases in polyplex affinity for collagen and the natural process of collagen remodeling.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, we demonstrated previously that GPP‐modification of PEI polyplexes greatly enhanced control over both the extent and duration of transgene expression through utilization of the reversible, serum‐stable affinity between CMPs and natural collagen. Enhanced control and activity were demonstrated both in vitro and in vivo, using a murine subdermal repair model . Additional studies concluded that these improvements were the result of superior serum‐stability and endocytic trafficking driven by increases in polyplex affinity for collagen and the natural process of collagen remodeling.…”
Section: Discussionmentioning
confidence: 96%
“…Through varying CMP display, DNA release/retention was tailored for over a month, two times longer than the retention/release periods of unmodified polyplexes. CMP‐modification also maintained polyplex activity in serum‐supplemented media for up to 2 weeks, in contrast with most gene delivery approaches which report losses to nuclease degradation within hours . Additionally, we demonstrated the novel ability to “hijack” collagen remodeling, a process that occurs in excess in the protease‐rich chronic wound environment .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In vitro wound closure with PDGF polyplexes was improved by 2-fold and 2.5-fold with 20% CMP-PEI polyplexes and mixed polyplexes (20% CMP-PEI and 50% CMP-PEI mixtures), respectively, as compared to non-CMP-modified polyplexes [47]. On-demand polyplex release and gene expression delivery was also were demonstrated in vivo , wherein gene expression could be tailored to peak at 6-20 days depending on the levels of CMP modification [48]. …”
Section: Peptides For Spatiotemporally-controlled Gene Deliverymentioning
confidence: 99%
“…Custom proteins are finding increased utility in advanced material fields such as gene delivery (Urello, Kiick, & Sullivan, ), biomaterials (Hu, Cebe, Weiss, Omenetto, & Kaplan, ; Yang, Holmberg, & Olsen, ), enzyme design (Siegel et al, ), active peptide design (Ikonomova, Moghaddam‐Taaheri, Jabra‐Rizk, Wang, & Karlsson, ), and biosensors (Kallmyer, Musielewicz, Sutter, & Reuel, ; Pardee et al, ). In each case, the ability to quickly screen the phenotypic behavior of each candidate in a large library of proteins is critical to down‐select to a smaller pool for expression optimization and purification.…”
Section: Introductionmentioning
confidence: 99%